2001
DOI: 10.1046/j.1365-2699.2001.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and ecology of paedomorphosis in Triturus alpestris (Amphibia, Caudata)

Abstract: Aim Paedomorphosis is an evolutionary change in which larval structures are retained in adult animals. In newts and salamanders, this heterochronic process is widely represented and concerns the retention of gill slits. We want to ®nd out whether ecological and geographical determinants may be associated with paedomorphosis in the Alpine newt Triturus alpestris.Location Europe.Methods Determination of the main characteristics of all known aquatic sites containing paedomorphic Alpine newt individuals.Results Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…This association between polyphenic expression and habitat characteristics has been suggested in ambystomatid salamanders in North America (Rose and Armentrout 1976;ShaVer 1984;Semlitsch and Gibbons 1985;Ryan and Semlitsch 1998). On the other hand, ecological parameters of aquatic and terrestrial environments do not explain the patterns of polyphenic expression in alpine newt, Triturus alpestris (Denoël et al 2001a). Resource competition within populations likely explains maintenance of life cycle polyphenism in this species (Denoël and Joly 2001;Denoël et al 2004).…”
Section: Discussionmentioning
confidence: 67%
“…This association between polyphenic expression and habitat characteristics has been suggested in ambystomatid salamanders in North America (Rose and Armentrout 1976;ShaVer 1984;Semlitsch and Gibbons 1985;Ryan and Semlitsch 1998). On the other hand, ecological parameters of aquatic and terrestrial environments do not explain the patterns of polyphenic expression in alpine newt, Triturus alpestris (Denoël et al 2001a). Resource competition within populations likely explains maintenance of life cycle polyphenism in this species (Denoël and Joly 2001;Denoël et al 2004).…”
Section: Discussionmentioning
confidence: 67%
“…One lake is located in southern France (La Cabane,4424 The three populations are composed of syntopic paedomorphic and metamorphic newts (Denol et al 2001a). In paedomorphic newts, the gill slits are open and support three pairs of external gills.…”
Section: Methodsmentioning
confidence: 99%
“…For example, predation on newts could be intensive in large ponds, while in smaller ponds predation could be limited or even absent because most of the time the newts are the major predators (e.g. Cooke & Frazer 1976;Giacoma et al 1988;Bringsøe 1994;Denoël et al 2001). It has been reported that intensive predation on Appendix I.…”
Section: Body Size Variation: Influence Of the Habitatmentioning
confidence: 99%